The Fiscal Policy and Tax Implications for Medical Device Resilience in Indonesia - Adji, Arga Setyo; Maulana Satrioaji, Abdillah; Haksama, Setya; Dwi Purwanto, Andi (PT ARRUS Intelektual Indonesia, 2025)
The high degree of dependence on imported medical devices in Indonesia poses challenges to national resilience in the healthcare sector. Fiscal policies, including taxation regulations, fiscal incentives, and import substitution strategies, play a significant role in enhancing the competitiveness of the domestic medical device industry. This study employs a normative method with a legislative approach to analyse the impact of taxation regulations on the competitiveness of the medical device industry. The findings indicate that 1) import duties regulated under PMK No. 26/PMK.010/2022 provide protection for local products but require synergy with fiscal incentives, as outlined in PP No. 45 Tahun 2019; 2) import substitution policies have successfully increased local production but are still constrained by dependence on imported raw materials; 3) tax regulations, such as Article 22 of Law No. 36/2008 and the imposition of a 10% VAT, contribute to protecting the domestic market, but the tax burden on end consumers remains a challenge; and 4) a more integrated and sustainable fiscal policy framework is needed to foster innovation, efficiency, and acceleration of the independence of the medical device industry in Indonesia. This study highlights the importance of strengthening fiscal regulations to support the resilience of the national healthcare sector.